Hubungan Kepuasan Mutu Pelayanan Immunisasi Dasar Terhadap Loyalitas Ibu Balita - Christin Hiyana Tunggadewi; Siti Rofi'ah; Arum Lusiana (JURNAL KEBIDANAN, 2019)
Immunization is an attempt to provide immunity to infants and children by inserting vaccines into the body so that the body makes substances anti to prevent certain diseases. The purpose of immunization is to stimulate the body's immunological system to form specific antibodies so that it can protect the body from attacks that can be prevented by immunization (PD3I)(Lestari W, Margawati A, 2014) In 2015, 292 districts / cities (56.8%) had reached 80% of complete basic immunization in infants, thus the target of the RPJMN in 2015 of 75% was not achieved(Kemenkes RI, 2015). This research is analytic survey with cross sectional approach. Samples were mothers of babies who came to the Puskesmas to get immunization services at Mungkid Health Center as many as 123 respondents. Bivariate analysis used statistical tests Chi-Square.The results showed that the satisfaction of the quality of basic immunization services for mothers of children under five was mostly in the category of 105 respondents satisfied (85.4%), the loyalty of mothers of children under five in the immunization category was 133 respondents (91.9%) and there was no relationship between satisfaction quality of basic immunization services with maternal loyalty of children under five in immunization with p-value = 0.163. Puskesmas to provide information, especially about side effects or information related to post-immunization follow-up events to reduce anxiety rates for mothers who will do immunization.